AB0661 Predictors of Response in Patients with Ankylosing Spondylitis Treated with Infliximab or Golimumab in A Real-World Setting. (15th July 2016) - Bessette, L.; Kapur, S.; Zummer, M.; Starr, M.; Choquette, D.; Sheriff, M.; Olszynski, W.; Rampakakis, E.; Psaradellis, E.; Osborne, B.; Maslova, K.; Nantel, F.; et al.
Abstract : Background: Recent studies have suggested that early and aggressive treatment of spondyloarthritis, including ankylosing spondylitis (AS) and psoriatic arthritis (PsA), may be associated with favorable patient outcomes, reducing synovial inflammation, delaying joint damage, and maintaining functional status. Objectives: The objective of this analysis was to determine the predictive factors of ASDAS remission in AS patients treated with infliximab (IFX) or golimumab (GLM) in a Canadian routine clinical care setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis, or psoriatic arthritis with IFX or GLM. Eligible patients for this analysis included AS patients treated with IFX or GLM between 2005 and 2015. Variables associated with ASDAS remission (<1.3) were examined using univariate analysis and those showing a statistical trend (P<0.150) were considered in multivariate logistic regression analysis to identify independent predictors. Results: A total of 582 patients were included in the analysis with a mean (SD) age of 45.8 (12.2) years and a disease duration of 8.3 (10.2) years. The majority of patients were male (57.2%). Upon 12 months of treatment statistically significant and clinically meaningful improvements were observed in ASDAS (3.6 vs. 2.3; P<0.001), BASDAI (6.2 vs. 3.8; P<0.001), BASFI (5.6 vs. 3.9; P<0.001), morning stiffness (74.2 vs. 42.8; P<0.001), and HAQ-DI (1.12 vs. 0.77; P<0.001). The proportion of patients who achieved ASDAS remission was 22.3% and 22.2% at 6 and 12 months, respectively. Sustained remission was achieved by 16.0%. In univariate analysis, male gender (male vs. female: 25.2% vs. 14.1%; P=0.073), previous use of a biologic (experienced vs. naive: 37.5% vs. 20.9%; P=0.129), lower ESR (P=0.096), lower BASFI (P=0.003), lower BASDAI (P=0.002), lower morning stiffness (P=0.120) and lower HAQ-DI (P=0.001) showed a statistical trend in their association with ASDAS remission at 12 months of treatment. Age, disease duration, CRP, psoriasis, peripheral arthritis, inflammatory bowel disease, uveitis, HLA-B27 and presence of enthesitis did not have an impact of ASDAS remission. Multivariate logistic regression analysis showed that, upon adjusting for covariates, non-exposure to a previous biologic (OR=3.40; P=0.078) approached statistical significance and lower HAQ-DI (OR=0.36; P=0.004) was a significant independent predictor of ASDAS remission. Conclusions: Twelve-month treatment with IFX or GLM in a real-world setting was associated with significant improvements in disease parameters. Prior exposure to a biologic and lower HAQ-DI were identified as independent predictors of ASDAS remission upon adjusting for potential confounders. Disclosure of Interest: L. Bessette: None declared, S. Kapur: None declared, M. Zummer: None declared, M. Starr: None declared, D. Choquette: None declared, M. Sheriff: None declared, W. Olszynski: None declared, E. Rampakakis Employee of: JSS Medical Research Inc;, E. Psaradellis Employee of: JSS Medical Research Inc;, B. Osborne Employee of: Janssen, K. Maslova Employee of: Janssen, F. Nantel Employee of: Janssen, A. Lehman Employee of: Janssen, C. Tkaczyk Employee of: Janssen